Identification and temporal trends of patients with neuromyelitis optica spectrum disorder in a US insurance claims database. (1st January 2021) - Exuzides, Alex; Wu, Ning; Sheinson, Daniel; Flores Avile, Carlos; Costantino, Cristina; Sidiropoulos, Paris
Abstract: Background: This US claims-based study aimed to identify and characterize temporal trends in diagnostic pathways for patients likely to have neuromyelitis optica spectrum disorder (NMOSD). Methods: Patients were identified from IBM MarketScan Commercial Databases if, within 1 year, they had two NMOSD claims separated by ≥ 60 days; two transverse myelitis (TM) or optic neuritis (ON) claims separated by ≥ 60 days, and one additional symptom (TM, ON, or area postrema syndrome); or one NMOSD claim and one additional symptom. The first NMOSD or TM/ON claim was the index date, and the second claim was the diagnosis date. Similar methodology was used in temporal trend and incidence and prevalence analyses. Results: Among 1, 901 patients with NMOSD, 34.2% were identified by two NMO claims, 53.2% by ON or TM +1 symptom, and 12.6% by one NMOSD claim +1 symptom. Anti–aquaporin-4 immunoglobin G (AQP4-IgG) autoantibody tests and magnetic resonance imaging was used for 23.0% and 71.9% of cases, respectively. Across cohorts, 21.4–49.1% had multiple sclerosis (MS) diagnosis claims prior to index date, and 37.3–60.6% had an MS diagnosis, 14.9–31.0% had MS disease-modifying therapy (DMT) claims and 6.3–44.8% had immunosuppressive therapy (IST) claims <1 year after diagnosis. Over time, there were slight changes in MS diagnosis claims, AQP4-IgG autoantibody testing, and DMT and IST use before and after NMOSD diagnosis. Limitations: This study is limited by the information available in US claims databases, which included the potential for misclassification of NMOSD based solely on claims codes and lack of reimbursement for AQP4-IgG testing by insurance companies. Conclusions: Among patients likely to have NMOSD, low AQP4-IgG testing rates, IST use, frequent MS diagnosis claims, and DMT use highlight the need for a diagnostic algorithm and timely treatment of NMOSD.